Perbanyakan Agens Hayati Beauveria Bassiana sebagai Biopestisida Ramah Lingkungan di Desa Sukatani, Kecamatan Compreng, Subang - Rohmah, Syifa Nur; Putri, Dhea Ananda; Rinsky, Eflyn Viola; Adly, Muhammad Naufal; Raadi, Asyura Zahra Lutffia; Permana, Sulaiman Hadi; Firamadhan, Fadlika Aliya; Karunia, Mutiara; Marwiyah, Siti; Priyambodo, Swastiko (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
Sukatani Village, Compreng Subdistrict, Subang Regency, faces the problem of decreased rice productivity due to pest attacks such as rice leafroll caterpillars (Cnaphalocrocis medinalis), walang sangit (Leptocorisa oratorius), and brown planthoppers (Nilaparvata lugens). As an effort to control pests that are environmentally friendly, counseling and training on the use of the biological agent Beauveria bassiana, an entomopathogenic fungus that is effective in controlling plant pests, was conducted. This activity aims to increase farmers' knowledge and capacity in producing and using biopesticides independently, in order to reduce dependence on chemical pesticides. The methods used include counseling, practice of making biopesticides, demonstration plots to test the effectiveness of Beauveria bassiana application on agricultural land, and provision of recommended doses. Data were collected through field observations, interviews with farmers and POPT officers, and literature studies. The results of the activity showed that the use of Beauveria bassiana can reduce pest populations without having a negative impact on the environment. The enthusiasm of farmers in participating in the training shows great potential for the implementation of sustainable agriculture. Sukatani Village is expected to become a pilot in the application of environmentally friendly biopesticide technology in the agricultural sector.